Formation of the system of organizational and economic support of innovative relations in Ukraine - Бабай, Дар’я Олегівна (Problems of legality, 2018)
The article deals with the formation of the optimal mechanism of economic and legal support of the state innovation policy, the definition of the subject, and would perform a general and leading role for the national innovation system. Determination of the status for other subjects of organizational and economic powers, which will be subordinated to the governing body. The question is that the system of organizational and economic support of innovative relations in Ukraine is not fully developed and requires optimization. So, until about 2010 there was one structure of the system of subjects of organizational and economic powers in the innovation sphere, and in the subsequent period it was subjected to significant transformations, therefore it is important to establish which functions and tasks, means and authorities, and place in the system of executive bodies the power is occupied and executed by each of the subjects of organizational and economic powers, both today and in retrospect, taking into account the assessment of their effectiveness. The purpose of this article is to work out approaches to optimizing organizational and economic support by comparing the structure of the system of subjects of organizational and economic powers in the innovation sphere that operated in the period until 2010 and after 2010, and the development of appropriate conclusions to improve the effectiveness of such a system as a whole. Thus, it seems expedient to distribute the system of public authorities in terms of organizational and economic powers in the innovation sphere for the period until 2010 and after 2010. Thus, the following bodies can be referred to the system that was until 2010: State Agency for Investments and Innovations, Ministry of Industrial Policy, Ministry of Education and Science, Ministry of Education in the field of intellectual property, National Council for Innovative Development, Ministry of Economy of Ukraine. The modern system looks like this now: the State Agency for Investments and Innovations, the Ministry of Education and Science, the Ministry of Economic Development and Trade of Ukraine, the Council for the Development of Innovations. However, even then, this system can not be called optimal. Since, firstly, they do not have a main body that would focus the final powers in themselves and accordingly coordinate these directions in these activities. Secondly, the optimization of the structuring of state bodies subordinate to the main body, depending on two basic criteria: - the elements-blocks of the scientific and innovation system and - the sector and the branch of the national economy. That is, the competence bodies with organizational and economic powers have the subject matter to have basic blocks, such as: scientific and technical activities, a unit for the creation of innovative products, a unit for the introduction of these products, a commercialization unit, and the like. The second criterion is the defense-industrial complex, the pharmaceutical industry, the machine-building industry, the agricultural sector, and the like.